(3GdZhGeV hGdeHgeGJ ef GdCSeGAs - (3GHf HTchGd , Nda Hf YHO Gdedc Hf eSYhO Hf HTchGd GdNRQLj GdCfUGQj, CHhGdbGSe,J (B578 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOi ef TGA HaVdg s
(3ai KdGKI YTQ LRAkGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B340 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B193 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1213s
Keywords: (3GdJGQjNs